Tinjauan Yuridis Pelanggaran Hak Perlindungan Anak: Analisis Kasus Kekerasan oleh Aparatur Dinas Perlindungan Anak - Rafaiyah, Shabrina Adilah Rafaiyah; Eny Nur Aisyah (Pro Justicia: Jurnal Hukum dan Sosial, 2025)
This study examines cases of violence against children committed by civil servants at the Medan City Women's Empowerment and Child Protection Agency, which raises profound contradictions because the perpetrators come from an institution whose main responsibility is to protect children. This study aims to evaluate the implementation of child protection laws and the legal and ethical accountability of state officials in relation to these incidents. The method used is a normative juridical approach through the analysis of legislation, legal principles, and scientific literature to assess the conformity between normative provisions and their implementation in practice. The findings show that although child protection regulations have been comprehensively formulated, their implementation has not been effective when violations are committed by public officials who are supposed to carry out protective functions. The perpetrator's actions not only violated criminal provisions but also contradicted the principles of integrity, professionalism, and responsibility that must be upheld by state officials. In addition, the study identifies a discrepancy between written law and law enforcement practices, as evidenced by weak internal oversight, a tendency toward reactive legal responses, and suboptimal efforts to provide redress to victims. This study concludes that strengthening child protection requires consistent law enforcement and accountability mechanisms.